Skills-First Approach in the Context of the Twin Transition - PASNICU, Daniela (Journal of Economic Development, Environment and People, 2023)
Skills, reskilling and higher qualifications have become increasingly important in the labor market as a result of the labor shortage faced by economic agents. This labor shortage is due to the effects of the twin ecological and digital transitions, demographic aging and the speed with which skill requirements in the labor market are changing and will trigger significant changes in the labor market. The aim of the paper is to understand the changes on the labor market in the context of the acceleration of twin transitions and how the skills-first approach could improve this transition in Romania. After reviewing the specialized literature and presenting the theoretical framework, the evolution of the Beveridge Curve in the period 2008-2022 and the social impact of the twin transition will be analyzed. The results underline the maintenance of the low capacity of the economy to create new jobs, as well as the large number of people without a job in the period 2020-2022. The top skill required on the labor market is the use of digital tools and top occupations in this skill are of ICT professionals, researchers, engineers.